(untitled) (Research, Society and Development, 2022)
To evaluate, describe and compare the pharmacological treatments available for heart failure (HF). This is a literature review about the pharmacological treatment of HF based on articles selected from the PubMed database, as well as relevant guidelines, using pertinent keywords and application of inclusion and exclusion criteria. Chronic heart failure is a common condition that, if untreated, harms quality of life and is associated with a high risk of mortality, morbidity, and recurrent hospitalization. However, the prognosis of patients with this condition has been improved with knowledge of the pathophysiology of HF and, therefore, assertive application of both non-pharmacological and pharmacological treatment recommendations. Pharmacotherapy is based on neurohormoral inhibition of the renin-angiotensin-aldosterone system (RAAS) and the sympathetic nervous system to improve the health status and survival of these patients. Currently, the recommendation for the treatment of HF with reduced ejection fraction (HFrEF) includes 4 drug classes: an angiotensin/neprilysin receptor inhibitor (ANRi), beta-blockers, mineralocorticoid receptor antagonists (MRA) and SGLT2 inhibitors (SGLT2ii). Mortality-reducing pharmacotherapy in HF currently includes ANRi, beta-blockers, MRA and SGLT2. Therefore, the challenge is to transform the results achieved in clinical studies into reality for the majority of patients with HF. This path must be promoted through multidisciplinary care with improved access to recommended drugs, close monitoring of patients, healthy habits, control of comorbidities and therapeutic adherence.